Low temperature bainitic ferrite: Evidence of carbon super-saturation and tetragonality. (1st June 2015) - Garcia-Mateo, C.; Jimenez, J.A.; Yen, H.-W.; Miller, M.K.; Morales-Rivas, L.; Kuntz, M.; Ringer, S.P.; Yang, J.-R.; Caballero, F.G.
Abstract: Experimental evidence indicates that bainitic ferrite formed by transformation at low temperatures (200–350 °C) contains quantities of carbon in solid solution far beyond those expected from para-equilibrium. A change in the conventional symmetry of the bainitic ferrite lattice from cubic to tetragonal explains the abnormal solid solubility detected. This carbon supersaturation was measured by atom probe tomography, and the tetragonality of the bainitic ferrite, was characterized by means of X-ray diffraction analysis and high resolution transmission electron microscopy.